Sex Differences in Behavioral Impulsivity in At-Risk and Non-Risk Drinkers - Weafer, Jessica; De Arcangelis, Jessica; de Wit, Harriet (Frontiers in Psychiatry, 2015)
Introduction: Mounting evidence from both animal and human studies suggests that females are more vulnerable to drug and alcohol abuse than males. Some of this increased risk may be related to behavioral traits, such as impulsivity. Here we examined sex differences in two forms of behavioral impulsivity (inhibitory control and impulsive choice) in young men and women, in relation to their level of alcohol consumption and alcohol-related problems (at-risk or non-risk). Methods: Participants performed a go/no-go task to assess inhibitory control and a measure of delay discounting to assess impulsive choice. Results: On the measure of inhibitory control, at-risk women committed significantly more inhibitory errors than at-risk men, indicating poorer behavioral control among the women. By contrast, no sex differences were observed between at-risk men and women in delay discounting, or between the male and female non-risk drinkers on any measure. Conclusion: Heavy drinking women displayed poorer inhibitory control than heavy drinking men. It remains to be determined whether the sex differences in inhibitory control are the result of drinking, or whether they pre-dated the problematic drinking in these individuals.